Pengaruh Literasi Keuangan, Fear of Missing Out (FOMO), dan Gaya Hedonisme terhadap Perilaku Keuangan Mahasiswa - Ghazlina Himaya; Syaiful Syaiful (Jurnal Kendali Akuntansi, 2026)
This study purpose to analyze the impact of financial literacy, FOMO, and hedonism on the financial behavior of e-wallet users at the University of Muhammadiyah Gresik. Questionnaires were distributed to 60 active students selected using a purposive sampling method using a quantitative survey approach. Data were analyzed through validity and reliability tests, classical assumption, multiple linear regression analysis, t and F tests, and coefficients of determination using IBM SPSS Statistics. The study results show that financial literacy significantly positively influences students' financial behavior, while FOMO and hedonism do not have a significant influence. These findings explain that the higher the level of financial literacy of students, the better their financial behavior in managing finances in the digital era. This finding is expected to serve as a guideline for developing financial management knowledge and even provide input for students to optimize financial literacy so they can manage their finances more wisely despite the development of digital technology and the ease of using e-wallets.